BIM as a strategic tool for supply chain in main projects in the United Kingdom - Moreira, Ana Gabriela de Barros Lopes (2017)
The need to achieve more efficiency and quality, reduce costs, cut carbon dioxide emissions and faster delivery were demanding for a vast change in the construction industry in the United Kingdom. To helping achieve these aims, as well be and remains in the vanguard of smart construction and digital design, UK made the decision to embrace Building Information Modelling (BIM), underpinned with the Government’s mandate launched in 2011, for Level 2 BIM compliance as minimum for all their centrally-procured projects by 2016. That decision resulted in a Government push to upskill the construction industry with the intention of reducing the capital and revenue costs associated with the procurement and use of buildings and infrastructure. For the public sector, BIM is offering the Government the opportunity to industrialise and reform its built environment through a digitally enabled procurement. Indeed, this Level 2 BIM programme already helping significant savings of circa £2.2bn between 2013 and 2015, making it a significant tool to meet the Government’s target of 15-20% savings on public construction costs (Cabinet Office, 2015). To support the industry to comply with Level 2 maturity, BIM Task Group and British Standard Institute, have developed several standards, documents and guides to explain clearly how BIM should be applied. The Level 2 programme is a key enabling strategy for the UK developing processes for data deliveries, classification and open data definitions. Certainly, the UK BIM standards and processes are working as a world-wide acknowledged benchmark for industry digitisation. By 2020, economists estimated that the UK market for BIM-related services will be an annual £30bn; in a global context, UK-based firms already export £7bn of architectural and engineering services; develop BIM capabilities and have a leadership position regarded to BIM, will provide UK further export growing and enable the industry to deliver higher quality and a more sustainability built environment for the future generations. This dissertation aim to encourage everyone to learn more about building information modelling and to explore the success example of the UK strategy Government related to BIM level 2 mandate. For that purpose, this document first explains the fundamental concepts of BIM and then explores the context in the UK: BIM maturity levels, the existing codes and standards, addresses the named “8 pillars of Level 2 BIM” and explains the information delivery cycle process. It also becomes relevant discuss in this paper, the current situation of the BIM adoption by the AEC industry and address some of the benefits and limitations of BIM adoption in the country. Furthermore, we look beyond and investigate the BIM level 3. The research has been conducted by an extensive review on the literature related to the topic of interest, collecting and analysis of surveys that have been conducted related to BIM in the UK and experienced working in a UK based contractor. A case of study is showed to recognise the importance of use BIM for a large project such as the High Speed 2, and additionally it is suggested a process map for BIM execution planning.